г. ) . ,

  1. OCHOBHO в в . в
  2. ) .
  3. ) '
  4. .
  5. . г . .
  6. . .

1 . , 1 (1 + 2i). г .

z : z = x + yi.

, , x = 3/2. ϳ , y: ; , . , , .

) z x ? y. г ().

)

.

, , , (2 - 3i), 1, 2.

2.

( ) ,

, (2)

- ³ (), 0, z - . f (z) deg f (z).

.

z0 f (z), f (z0) = 0.

1 ( ). - f (z) g (z) h (z) r (z) , :

1) f (z) = h (z) g (z) + r (z),

2) deg r (z)

h (z) r (z) .

h (z) , r (z) - f (z) g (z). , deg f = deg g + deg h. r (z) ? 0, , f (z) g (z).

2. z0 f (z) , f (z) (z - z0).

z0 m f (z), f (z) (z - z0)m (z - z0)m+1. , , : z0 m f (z), f (z) f (z) = (z - z0)mg (z), g (z) - , g (z0) ? 0.

3 ( ). n ? 1 n , , .

, z1, z2, ..., Zm- (1) k1, k2, ..., Km, f (z)

,

, k1+ k2+ ... + Km= N.

(P - , q - ) f (z) aj, , p a0, q - n. , f (z) aj an= 1, , a0 .

4. f (z) - z0 = a + ib - f (z), 'z0= A - ib .

, f (z) - ,

, (3)

zj, pj, qj- ij (. . ), .

k1+ k2+ ... + Km+ 2 (r1+ r2+ ... + Rs) = N.

f (z), g (z) - , . , deg g (z) <

. (4)

z g (z) , (3) ( ).

1. , .

г.f (z) , z1= 2 + i f (z) z2= 'Z1= 2-i. , f (z) .

f (z)

, . : z2+ 2z + 10 = 0, z3,4= -1 3i. , f (z) : z1= 2 + i, z2= 2 - i, z3= -1 - 3i, z4= -1 + 3i. f (z) ( ) : z4- 2z3+ 7z2- 30z + 50 = (z2- 4z + 5) (z2+ 2z +10).

2. f (z) = z4- 6z3+ 10z2+ 2z - 15:

) ;

) f (z) ;

) f (z) ;

) (2z - 3) / f (z) .

г.) 15 : 1, 3, 5, 15.

, z1= -1 f (z):

f (-1) = 0. , f (z)

(Z - z1) = Z + 1.

: f (z) = (z + 1) (z3- 7z2+ 17z - 15). (-15): 1; 3; 5; 15.

, (z3- 7z2+ 17z - 15) , , f (z). , f (z) (z - z1) (Z - z2) = (Z + 1) (z - 3) = z2- 2z - 3. f (z) :

, f (z) = (z2- 2z - 3) (z2- 4z + 5). (z2- 4z +5) ( ) . , f (z) : z1= -1 z2= 3.

) z2- 4z + 5 = 0 , ;

) f (z) 4 (, ) : z1= -1,

z2= 3, z3= 2 - i, z4= 2 + i. f (z) 1. f (z) = (z - z1) (Z - z2) (Z - z3) (Z - z4) f (z) = (z + 1) (z - 3)

(Z - 2 + i) (z -2- i);

) (2z - 3) / f (z) .

.

:

f (z) ,

A (z -3) (z2- 4z +5) + B (z + 1) (z2- 4z +5) + (Cz + D) (z +1) (z - 3) 2z - 3.

, , , D , , z , 4- :

(A + B + C) z3+ (- 7A - 3B - 2C + D) z2+ (17A + B - 3C - 2D) z +

+ (- 15A + 5B - 3D) = 2z - 3.

z,

, A = 1/8, B = 3/8, C = -1/2, D = 1. , .

1.1

, .

1) z1= -2 + I, z2= 4 - 3i; 16) z1= 6 - i, z2= -2 + 3i
2) z1= 3 - 2i, z2= 2 + 5i; 17) z1= -3 + I, z2= -1 - 3i;
3) z1= -4 + I, z2= 5 - 2i; 18) z1= 2 + 4i, z2= -5 - 3i;
4) z1= -1 + 3i, z2= -3 + 2i; 19) z1= -3 + 4i, z2= 5 + 4i;
5) z1= 7 + 2i, z2= -6 - I; 20) z1= 1 - 5i, z2= -4 - I;
6) z1= 4 + 3i, z2= -2 + 5i; 21) z1= -5 + 4i, z2= 2 -i;
7) z1= -2 - 3i, z2= 3 - 4i; 22) z1= -4 + 5i, z2= 1 + 6i;
8) z1= 2 + i, z2= -3 - 2i; 23) z1= -2 - 5i, z2= 5 - 4i;
9) z1= -3 - 4i, z2= 1 - 3i; 24) z1= 3 + 4i, z2= -2 - I;
10) z1= 2 + 3i, z2= -4 - 2i; 25) z1= 3 + 2i, z2= -5 - I;
11) z1= 5 + i, z2= - 4 - 3i; 26) z1= -1 + 5i, z2= 3 - i;
12) z1= -6 + I, z2= -2 - 2i; 27) z1= 1 - 2i, z2= -2 + 6i;
13) z1= -5 + 3i, z2= -5 - 2i; 28) z1= 1 + 3i, z2= -5 + I;
14) z1= 2 - 4i, z2= -3 + 5i; 29) z1= -6 - 2i, z2= 4 + 5i;
15) z1= -4- 5i, z2= 4 + 2i; 30) z1= -5 - 4i, z2= 6 + 2i.

1.2

.

1) 2z2+ 3z + 4 = 0; 7) 2z2+ 5z + 7 = 0;

2) z2- 2z + 2 = 0; 8) -4z2- 4z - 3 = 0;

3) z2+ 5z + 8 = 0; 9) 3z2+ 2z + 9 = 0;

4) z2- 4z + 13 = 0; 10) 4z2+ Z + 2 = 0;

5) -z2+ Z - 2 = 0; 11) -z2- Z - 3 = 0;

6) z2- 2z + 7 = 0; 12) 2z2- 4z + 5 = 0;


13) 2z2- 2z + 5 = 0; 22) 6z2- Z + 1 = 0;

14) -2z2- Z - 1 = 0; 23) -3z2+ 2z - 1 = 0;

15) z2- 6z + 10 = 0; 24) -2z2- 8z - 15 = 0;

16) 4z2- 2z + 1 = 0; 25) z2- 2z + 7 = 0;

17) 2z2+ Z + 5 = 0; 26) -6z2- Z - 1 = 0;

18) 5z2+ Z + 1 = 0; 27) 2z2+ 6z + 11 = 0;

19) -3z2+ 4z - 2 = 0; 28) -3z2+ 6z - 10 = 0;

20) z2- 4z + 20 = 0; 29) 4z2- 8z + 13 = 0;

21) -6z2+ 4z - 3 = 0; 30) z2+ 4z + 17 = 0.

1.3

䳿. ³ .

1.4

. , .

1) ; 10) ;

2) ; 11) ;

3) ; 12) ;

4) ; 13) ;

5) ; 14) ;

6) ; 15)

7) ; 16) ;

8) ; 17) ;

9) ; 18) ;

19) ; 25) ;

20) ; 26) ;

21) ; 27) ;

22) ; 28) ;

23) ; 29) ;

24) ; 30) .

1.5

: ) ; ), ) ().

1. a) ) ; ) ;

2. a) ) ; ) ;

3. a) ) ; ) ;

4. a) ) ; ) ;

5. a) ) ; ) ;

6. a) ) ; ) ;

7. a) ) ; ) ;

8. a) ) ; ) ;

9. a) ) ; ) ;

10. a) ) ; )

11. a) ) ; ) ;

12. a) ) ; )

13. a) ) ; )

14. a) ) ; )

15. a) ) ; ) ;

16. a) ) ; ) ;

17. a) ) ; )

18. a) ) ; ) ;

19. a) ) ; )

20. a) ) ; )

21. a) ) ; )

22. a) ) ; ) ;

23. a) ) ; ) ;

24. a) ) ; )

25. a) ) ; )

26). a) ) ; ) ;

27. a) ) ; )

28. a) ) ; )

29. a) ) ; )

30. a) ) ; )

1.6

, z1 .

1) , ;

2) , ;

3) , ;

4) , ;

5) , ;

6) , ;

7) , ;

8) , ;

9) , ;

10) , ;

11) , ;

12) , ;

13) , ;

14) , ;

15) , ;

16) , ;

17) , ;

18) , ;

19) , ;

20) , ;

21) , ;

22) , ;

23) , ;

24) , ;

25) , ;

26) , ;

27) , ;

28) , ;

29) , ;

30) , .

1.7

f (z) g (z): ) ϳ f (z) ; ) f (z) ; ) f (z) ; ) g (z) / f (z) .

1) f (z) = z4- 3z3+ z2+ 4, g (z) = z2- 2z - 3;

2) f (z) = z4- 4z3+ 2z2+ Z + 6, g (z) = z2- 2z - 4;

3) f (z) = z4- 5z3+ 3z2+2 Z + 8, g (z) = z2- 3z - 5;

4) f (z) = z4 - 2z2- 3 z - 2, g (z) = z2+ Z - 2;

5) f (z) = z4- 6z3+ 4z2+ 3z + 10, g (z) = z2- 5z - 6;

6) f (z) = z4- z3- 4z2- 5z - 3, g (z) = z2- 3z - 5;

7) f (z) = z4- 7z3+ 5z2+ 4z + 12, g (z) = z2- 6z - 5;

8) f (z) = z4- 2z3- 6z2- 7z - 4, g (z) = z2- 4z - 6;

9) f (z) = z4- 3z3- 8z2- 9z - 5, g (z) = z2- 5z - 7;

10) f (z) = z4- 4z3- 10z2- 11z - 6, g (z) = z2- 6z - 8;

11) f (z) = z4- z3- 2z2- 2z + 4, g (z) = z2- 2z - 3;

12) f (z) = z4- 3z3- 2z2+ 2z + 12, g (z) = z2- 3z - 3;

13) f (z) = z4- 2z3- 3z2- 2z + 6, g (z) = z2- 3z - 2

14) f (z) = z4- 4z3- 2z2+ 4z + 16, g (z) = z2- 4z - 2;

15) f (z) = z4- 3z3- 4z2- 2z + 8, g (z) = z2+ 4z -2;

16) f (z) = z4- 5z3- 2z2+ 6z + 20, g (z) = z2- 5z - 5;

17) f (z) = z4- 4z3- 5z2- 2z + 10, g (z) = z2- 5z - 6;

18) f (z) = z4- 6z3- 2z2+ 8z + 24, g (z) = z2- 6z -6;

19) f (z) = z4+ 3z3+ 2z2- 2z - 4, g (z) = z2- Z - 3;

20) f (z) = z4- 5z3- 6z2- 2z + 12, g (z) = z2- 6z - 6;

21) f (z) = z4+ 2z3- 2z2- 8z - 8, g (z) = z2- 2z - 4;

22) f (z) = z4+ z3- 6z2- 14z - 12, g (z) = z2- 3z - 3;

23) f (z) = z4- 3z3+ 4z2- 3z + 1, g (z) = z2- Z - 3;

24) f (z) = z4- z3- 3z2+ 4z - 4, g (z) = z2- 2z - 4;

25) f (z) = z4- 4z3+ 6z2- 5z + 2, g (z) = z2- 2z + 4;

26) f (z) = z4- 2z3- 4z2+ 5z - 6, g (z) = z2- 3z + 3;

27) f (z) = z4- 5z3+ 8z2- 7z + 3, g (z) = z2+ 3z - 3;

28) f (z) = z4- 3z3- 5z2+ 6z - 8, g (z) = z2- 4z - 4;

29) f (z) = z4- 6z3+ 10z2- 9z + 4, g (z) = z2+ 4z - 4;

30) f (z) = z4- 4z3- 6z2+ 7z - 10, g (z) = z2- 5z - 5.



I |
© um.co.ua -